2019
DOI: 10.4172/pharmaceutical-sciences.1000483
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Pictogram for Thai Patients with Low Literate Skills

Abstract: Low literacy is an important and widespread problem. Deficiencies in basic reading, communicating, and comprehension skills significantly affect the ability to function in daily life, particularly effective use of medicines, as patients cannot perform necessary functions in health care environment such as understanding the directions on the label on medication packages [1]. In 1990, the UNESCO reported 26.6 % of adults in the world were illiterate and of those 34.9 % were in developing countries [2]. Illiterac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…• Self-reported adherence was 0.5 points higher in ARMS score n the intervention group, though not statistically significant (95% CI, -0.1-1.1) • Patients in the intervention group had a higher mean percentage compliance score (88%) than the controls (66%) (p < 0.05) interventions employing pictograms (Machtinger et al, 2007;Negarandeh et al, 2013;Mohan et al, 2014;Phimarn et al, 2019), whereas, individuals with high health literacy do not seem to benefit to the same degree (Kripalani et al, 2012). Table 1 summarizes the results of studies on the use of pictograms among chronically ill patients in distinction for the following diseases: asthma (n 2), diabetes (n 4), AIDS (n 7), chronic kidney disease (n 1), and cardiac disorders (n 4).…”
Section: Pictograms In Health-related Research: a Focus On Chronic Patientsmentioning
confidence: 96%
See 1 more Smart Citation
“…• Self-reported adherence was 0.5 points higher in ARMS score n the intervention group, though not statistically significant (95% CI, -0.1-1.1) • Patients in the intervention group had a higher mean percentage compliance score (88%) than the controls (66%) (p < 0.05) interventions employing pictograms (Machtinger et al, 2007;Negarandeh et al, 2013;Mohan et al, 2014;Phimarn et al, 2019), whereas, individuals with high health literacy do not seem to benefit to the same degree (Kripalani et al, 2012). Table 1 summarizes the results of studies on the use of pictograms among chronically ill patients in distinction for the following diseases: asthma (n 2), diabetes (n 4), AIDS (n 7), chronic kidney disease (n 1), and cardiac disorders (n 4).…”
Section: Pictograms In Health-related Research: a Focus On Chronic Patientsmentioning
confidence: 96%
“…In patients living with chronic illness, data suggests that individuals with low health literacy can benefit more from interventions employing pictograms ( Machtinger et al, 2007 ; Negarandeh et al, 2013 ; Mohan et al, 2014 ; Phimarn et al, 2019 ), whereas, individuals with high health literacy do not seem to benefit to the same degree ( Kripalani et al, 2012 ). Table 1 summarizes the results of studies on the use of pictograms among chronically ill patients in distinction for the following diseases: asthma ( n = 2), diabetes ( n = 4), AIDS ( n = 7), chronic kidney disease ( n = 1), and cardiac disorders ( n = 4).…”
Section: What Is a Pictogram?mentioning
confidence: 99%
“…Most studies about pictograms used as communication tools focus on pictograms that depict pharmaceutical-and health-related information [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] or hazardous substances and their safe handling [7,[20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Pictograms are useful when communicating certain types of information for which language, literacy, and reaction times can be barriers [ 32 ]. For example, some studies have shown that pictograms are beneficial for facilitating danger recognition and the understanding of precautionary measures [ 5 , 7 , 8 , 12 , 13 , 18 , 22 , 31 , 33 ]. Some of the advantages of using pictograms instead of written words are that they can facilitate faster recognition and remembrance during a second encounter and can improve the understanding of communicated messages for people with visual deficiencies or low literacy levels and people who are unfamiliar with the language used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation